2016
DOI: 10.1177/1744806916649192
|View full text |Cite
|
Sign up to set email alerts
|

A pro-nociceptive phenotype unmasked in mice lacking fatty-acid amide hydrolase

Abstract: Fatty-acid amide hydrolase (FAAH) is the major enzyme responsible for degradation of anandamide, an endocannabinoid. Pharmacological inhibition or genetic deletion of FAAH (FAAH KO) produces antinociception in preclinical pain models that is largely attributed to anandamide-induced activation of cannabinoid receptors. However, FAAH metabolizes a wide range of structurally related, biologically active lipid signaling molecules whose functions remain largely unknown. Some of these endogenous lipids, including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…The subdivisions used were the superficial laminae (laminae I and II), the nucleus proprius (laminae III and IV), the neck of the dorsal horn (laminae V and VI) and the ventral horn (laminae VII, VIII, IX, and X) (Presley et al, 1990). Intraplantar injection of saline in lieu of formalin (n =3) did not induce appreciable expression of Fos-like immunoreactivity, consistent with the results of our previously published studies (Tsou et al, 1996, Nackley et al, 2003a, Nackley et al, 2003b, Carey et al, 2016) (data not shown).…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…The subdivisions used were the superficial laminae (laminae I and II), the nucleus proprius (laminae III and IV), the neck of the dorsal horn (laminae V and VI) and the ventral horn (laminae VII, VIII, IX, and X) (Presley et al, 1990). Intraplantar injection of saline in lieu of formalin (n =3) did not induce appreciable expression of Fos-like immunoreactivity, consistent with the results of our previously published studies (Tsou et al, 1996, Nackley et al, 2003a, Nackley et al, 2003b, Carey et al, 2016) (data not shown).…”
Section: Methodssupporting
confidence: 91%
“…Immunohistochemical experiments were conducted as previously described (Tsou et al, 1996, Nackley et al, 2003a, Nackley et al, 2003b, Carey et al, 2016). Transverse sections (3μm) of the L4-L5 lumbar spinal cord were cut on a cryostat and maintained in an antifreeze solution (50% sucrose in ethylene glycol and 0.1 M PBS) prior to immunostaining.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, lipoxin A4 preferentially enhances anandamide but not 2-AG signaling(28). However, FAAH and MGL also degrade lipid mediators that do not bind to cannabinoid receptors(8, 12, 44). Sustained inhibition of MGL does not desensitize CB1 receptors in brain regions relevant to catalepsy (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Showing that other types of pain sensitivity are also reduced in FAAH KO mice, pain behavior was attenuated in the formalin test [27]. Consequently, FAAH became a therapeutic target for chronic pain; however, limited analgesic efficacy of a FAAH inhibitor was found in a human clinical trial [45], which may be explained by the observation that FAAH deletion actually enhances some forms of pain [46]. Similarly to FAAH, MAGL is a potential drug target to treat pain.…”
Section: Introductionmentioning
confidence: 99%